(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2023)
The game theory framework can be used in a wide range of disciplines and case studies. The present work proposes the game theory approach and binomial grids, as strategic tools to analyze and evaluate the articulation and decision making of actors of the bovine livestock complex, specifically breeding and wintering. The originality arises from incorporating the strategic interdependence and articulations between players considering different scenarios of each particular business. The results allow us to conclude that a prisoner’s dilemma is reached from the differences between articulating through raised channels. The breeder, as an actor with less power, is the one who should guide greater efforts of direct articulation with the winterer.